FAKTOR – FAKTOR YANG BERHUBUNGAN dengan USIA MENOPAUSE (Studi di Puskesmas Bangetayu Tahun 2015) - Mujahidah Amrina Rosyada; Siti Fatimah Pradigdo; Ronny Aruben (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
The aging process occurs in human life . Especially in women , disruption to the loss of the normal process of menstruation is an issue that will be passed women because menopause is a physiological problem . Acceptance of menopause among women will be different and therefore the problem of factors related to the age of menopause should be known clearly by women. In PHC Bangetayu , from 15 to 40 % of women Whose menopause between the ages of 45-50 , and 60 % aged > 51 years. The aim of this study was to determine the factors associated with menopause . Is a quantitative research with cross sectional approach. The population in this study were women aged 40-59 years with a total of 60 people . The sampling technique in the research using purposive sampling . The data analysis used the chi square test and Spearman Rank test with significance level α = 5 %. The research showed that most of the samples with menopause age ≥ 50 years ( 58.3 % ) , the status of completed high school ( 31.7 % ) , having children > 4 ( 63.3 % ) , used contraception ( 86.7 % ) and experienced menarche at age > 16 years ( 71.7 % ) . The test results stating the relationship there is a correlation between the number of children with the age of menopause ( p = 0.046 ) and there is a correlation with age of menarche age of menopause ( p = 0.047 ) . This study concluded that factors associated with menopause age is the age of menarche and number of children. Suggestion for the Department of Health to to be more active in maternal and child health programs , especially older programs with the holding of Posyandu elderly . Expected the public to know the sense of menopause , menopausal symptoms , factors associated with menopause and know how to cope with the symptoms of menopause